2019
DOI: 10.2507/ijsimm18(4)492
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Method for Dropper Dynamic Load Considering Horizontal Vibration Behaviour

Abstract: Dropper is the key component of catenary in high-speed railways. The prediction of the fatigue life of dropper is accomplished using alternating load characteristics. Simulation method for obtaining the dynamic internal load of the dropper in previous studies was insufficient for accurate requirements in predicting dropper life. According to realistic working conditions in the simulation environment, this study proposed a simulation method considering horizontal vibration behaviour for the dropper. The horizon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The first-order change and second-order change of pixel gray value in the y-axis direction of the image are calculated by the formulas (17) and (18).…”
Section: Impact Displacement Excitationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first-order change and second-order change of pixel gray value in the y-axis direction of the image are calculated by the formulas (17) and (18).…”
Section: Impact Displacement Excitationmentioning
confidence: 99%
“…In addition, with the increase of contact wire tension, the stress amplitude and maximum stress of dropper decrease significantly. 16 Zhang et al 17 found that the lateral swing of the dropper in the process of vibration deformation has an important impact on the dropper stress through field measurement and simulation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The reserve capacity and expected profits of both parties with different payment schemes and information sharing strategies can be calculated, the influence of payment scheme and information sharing can be analyzed, and the range of t that can make HSR carrier and express service provider accept APS and encourage the express service provider to share information can be further determined. According to the actual operation data of the high-speed rail express [ 5 , 6 , 27 , 42 ], the relevant parameters were set as follows: , , , , , , , and , according to the feasible scope of t concluded in the present study, set .…”
Section: Impact Of Payment Scheme and Information Sharingmentioning
confidence: 99%
“…Vibrations in overhead contact systems are the main cause of wear in contact elements [9] and degradation of infrastructures [10] hence avoiding those oscillations will lead to greater lifetimes and reduction in maintenance activities. This reduction in times and expenses is the main objective of the elements described in this paper, based on its installation in existing infrastructures without changing the existing elements.…”
Section: Introductionmentioning
confidence: 99%